Antimicrobial properties of preterm breast milk cells. Issue 3 (March 1983) - Murphy, J F; Neale, M L; Matthews, N
Abstract : The antimicrobial properties of preterm and term breast milk cells were compared. They were similar in cell numbers and in the capacity to phagocytose and kill staphylococci. Interferon production on endotoxin challenge appeared to be higher in preterm cells. The antibacterial activity of breast milk cells was retained after storage at 4 degrees C for 24-48 hours. Cell numbers were unaffected by passage through a standard oral paediatric feeding set.